Analyzing Ethnocentric Immigration through the Case of Hungary – Demographic Effects of Immigration from Neighboring Countries to Hungary - Péti, Márton; Szabó, Laura; Obádovics, Csilla; Szabó, Balázs; Csécsi, Dávid (Journal of Ethnic and Cultural Studies, 2021)
Specific ethnocentric international migration processes can be observed in Hungary: a significant proportion of immigrants are of Hungarian ethnic background and come from neighboring countries. Similar processes can be observed between other kin-states and co-ethnic communities of Central and Eastern Europe, but this type of migration has not been studied intensively yet. The focus of the research is on the effects of this immigration on Hungarian society and the economy. Population projections were also carried out according to two research questions: “what would have happened if the immigrants had not arrived according to the processes that were experienced?” and “what will happen if the immigration process changes?” The research is based on the 2011 census data sets; the target group is the population born in neighboring countries that moved to Hungary after 1985. Results show that the ethnic Hungarian immigrant population has been a crucial human resource in Hungary. Without these immigrants, Hungary’s demographic trends would also be less favorable. Moreover, in contrast to the situation typical of European immigrants, the socio-economic situation of the former is more favorable than of the host society. Potential decline of this immigration population could indeed be challenging.